Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T20:42:28+01:00
A)
1-0,2x = 0,3x
-0,2x-0,3x=-1
-0,5x=-1/(-0,5)
x=2
b)
0,01x -1=0,1x - 0,1
0,01x-0,1x=-0,1+1
-0,09x=0,9/:(-0,09)
x=-10
c)
1/3 x-2=x+2
1/3x-x=2+2
-2/3x=4/(-2/30
x=-6
d)
? coś chyba źle wpisane
e)
6 ( 1/4x-2)=18
3/2x-12=18
3/2x=18+12
3/2x=30/: 3/2
x=20
f)
x/6 - 1/6 =1
1/6x=1+1/6
1/6x=1i1/6
1/6x=7/6/: 1/6
x=42/6
x=7
g)
-2 (2x-1) =x/3
-4x+2=1/3x
-4x-1/3x=-2
-4 i 1/3x=-2
-13/3x=-2/:(-13/3)
x=6/13
h)
2/5 (3-x) =-2
6/5-2/5x=-2
-2/5x=-2- 6/5
-2/5x=-3i 1/5
-2/5x=-16/5 /: (-2/5)
x=8
i)
3/4(2-3x) = -6
6/4-9/4x=-6
-9/4x=-6-6/4
-9/4x=-7i2/4
-9/4x=-30/4 /:(-9/4)
x=30/9
x=3i3/9
x=3i1/3
j)
1/5 (x-3) =9-x
1/5x-3/5=9-x
1/5x+x=9+3/5
1i1/5x=9i3/5
6/5x=48/5 /:6/5
x=8
k)
0,6 +x /2 = x+1
0,5x-x=1-0,6
-0,5x=-0,6/:(-0,5)
x=1,2
2010-03-14T20:46:17+01:00
A)1-0,2x=0,3x
1=0,5x
x=2
b)0,01x-1=0,1x-0,1
-0,09x=0,9
x=-10
c)1\3x-2=x+2
1\3x-3\3x=2+2
-2\3x=4
x=-6
d)chyba żle przepisane. nie ma x
e)6(1\4x-2)=18
6\4x-12=18
3\2x=30
x=20
f)x\6-1\6=1
x\6=7\6
x=7
g)-2(2x-1)=x\3
-4x+2=1\3x
-12\3x-1\3x=-2
-13\3x=-2
x=6\13
h)2\5(x-3)=-2
2\5x-6\5=-2
2\5x=-4\5
x=-2
i)3\4(2-3x)=-6
6\4-9\4x=-24\4
-9\4x=-15\4
x=15\9
j)1\5(x-3)=9-x
1\5x-3\5=9-x
1\5x+x=9+3\5
6\5x=48\5
x=8
k)0,6+x\2=x+1
1\2x-x=1-0,6
-1\2x=0,4
x=-0,8